Power shared is power gained - Nyoni, Sithembiso (Technical Centre for Agricultural and Rural Cooperation, 2001)
Development is empowerment, and that is not just a methodology or a development gimmick. Empowerment means that people get equipped to deal with their own situation in a practical and viable way. The first step towards empowerment is assisting...